Using Telemedicine in Practice: Implications for Workforce Development - Marshall, Alison; Bidmead, Elaine (International Journal of Practice-based Learning in Health and Social Care, 2018)
The aim of this article is to present a discussion of the impact of telemedicine on professional practice, and the implications for the workforce. Telemedicine, or the use of video-conferencing for remote consultations between clinician(s) and patients, is now a mature technology. Many pilot studies have taken place, generally showing positive benefits to patients. There is emerging evidence that the impact on staff is more mixed; with concerns about changes to job role, skills development, and poor understanding of the organisational benefits. Evidence also highlights enablers of successful telemedicine implementation, including senior leadership, peer motivation, understanding of patient benefits, and time for safe experimentation. Following a review of qualitative data from four case study telemedicine projects undertaken within the authors’ research group, evidence from published literature is discussed. The four projects explore telemedicine services provided between an acute hospital service and nursing homes (remote assessment of swallowing difficulties), an acute hospital service and home (video-link to renal patients undergoing home dialysis), between a specialist teaching hospital service and a district general hospital (fetal abnormalities ultrasound telemedicine clinic), and a survey of mental health professionals across acute and community services within a locality. The introduction of telemedicine at scale requires an organisational and system-level approach that recognises the specific challenges and issues for the workforce. Education and training need to be provided at all levels. In conclusion: there are significant opportunities to realise the benefits of remote consultations, to improve the patient experience and staff productivity, if workforce issues are addressed.